Mothers’ Age and Education Who Work in Health Facility Influenced Nutritive Feeding Choice - Karini Kaman; Regina Vidya Trias Novita; Paramitha Wirdani Ningsih Marlina (Media Keperawatan Indonesia, 2020)
The health worker services are a role model. Activities breastfeeding decline when mothers started to work after maternity leave. The purpose of this research is to analyze the factors relating to the mothers on the reproductive age who works in the hospital. The method of the research was quantitative with cross-sectional. The research used questioners and held on January-March 2020. Total sampling with 40 respondents.  The result showed two variables were significant. There are the age of the mothers with p-value with the p 0.044 < 0.05 and the level of mother education with the p 0.045 <0.05. The reproductive age and education significantly positive for history giving exclusive breastfeeding.  The mothers had chosen mix feeding for nutritive their babies.  The environment did not support, even mothers have enough for their knowledge so they decided to give formula. Although mothers have high of the level of education still give mix feeding because of back to work, have no support on breastfeeding and facility where the mothers work. Conclusion the health services such as in the hospital should give the employee specialized women who had reproductive age to support for example facilities for the breast pump, maternity leave policy, and finally could be breastfeeding exclusively.